A homomeric geranyl diphosphate synthase-encoding gene from Camptotheca acuminata and its combinatorial optimization for production of geraniol in Escherichia coli. (1st October 2017) - Yang, Lixia; Jiang, Liangzhen; Li, Wei; Yang, Yun; Zhang, Guolin; Luo, Yinggang
Abstract: Geranyl diphosphate (GPP), the unique precursor for all monoterpenoids, is biosynthesized from isopentenyl diphosphate and dimethylallyl diphosphate via the head-to-tail condensation reaction catalyzed by GPP synthase (GPPS). Herein a homomeric GPPS from Camptotheca acuminata, a camptothecin-producing plant, was obtained from 5′- and 3′-rapid amplification of cDNA ends and subsequent overlap extension and convenient PCR amplifications. The truncate CaGPPS was introduced to replace ispA of pBbA5c-MevT(CO)-MBIS(CO, ispA ), a de novo biosynthetic construct for farnesyl diphosphate generation, and overexpressed in Escherichia coli, together with the truncate geraniol synthase-encoding gene from C. acuminata (t CaGES ), to confirm CaGPPS-catalyzed reaction in vivo. A 24.0 ± 1.3 mg L −1 of geraniol was produced in the recombinant E. coli . The production of GPP was also validated by the direct UPLC-HRMS E analyses. The t CaGPPS and t CaGES genes with different copy numbers were introduced into E. coli to balance their catalytic potential for high-yield geraniol production. A 1.6-fold increase of geraniol production was obtained when four copies of t CaGPPS and one copy of t CaGES were introduced into E. coli . The following fermentation conditions optimization, including removal of organic layers and addition of new n -decane, led to a 74.6 ± 6.5 mg L −1 of geraniol production. The present study suggested that the gene copy number optimization, i.e., the ratio of tCaGPPS and tCaGES, plays an important role in geraniol production in the recombinant E. coli . The removal and addition of organic solvent are very useful for sustainable high-yield production of geraniol in the recombinant E. coli in view of that the solubility of geraniol is limited in the fermentation broth and/or n -decane.